2004
DOI: 10.1021/nl035009o
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement of Polymers with Carbon Nanotubes:  The Role of Nanotube Surface Area

Abstract: Tensile tests were carried out on free-standing composite films of poly(vinyl alcohol) and six different types of carbon nanotubes for different nanotube loading levels. Significant increases in Young's modulus by up to a factor of 2 were observed in all cases. Theories such as the rule-of-mixtures or the Halpin-Tsai-theory could not explain the relative differences between composites made from different tube types. However, it is possible to show that the reinforcement scales linearly with the total nanotube … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
340
2
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 472 publications
(359 citation statements)
references
References 24 publications
14
340
2
3
Order By: Relevance
“…Therefore, it can be counted as the primary motivation for nanocomposite development [28,29]. This parameter in addition to the stress transfer [28,30] is responsible for Bnew structural arrangement^at microscale in the composites.…”
Section: Effect Of Filler Size and Shapementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can be counted as the primary motivation for nanocomposite development [28,29]. This parameter in addition to the stress transfer [28,30] is responsible for Bnew structural arrangement^at microscale in the composites.…”
Section: Effect Of Filler Size and Shapementioning
confidence: 99%
“…It is defined as interfacial area of polymer-filler per unit volume and it is related to the density ratio of polymer matrix to the fillers, the concentration, and diameter of the filler [50]. In this regard, Cadek et al have shown that the reinforcement of polymer composites is linearly related to the overall interfacial area of fillers, meaning that the smaller fillers can have higher impact on the property of the final product [29].…”
Section: Noncovalent Interactionmentioning
confidence: 99%
“…Various methods to provide this repulsive potential have been explored. Nanotubes have been dispersed and stabilised with the aid of specific solvents [16][17][18][19][20][21][22][23][24] , acids [25,26] , macromolecules [27][28][29][30] and surfactants [31][32][33][34] as well as through covalent functionalisation strategies [35,36] . Such systems have been characterised by a range of techniques such as atomic force microscopy [37] , infra-red photoluminescence and absorbance spectroscopy [34] , viscometry [25] , small angle neutron scattering [32] to name but a few.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some progress has been made using polymer solution based processing to organize nanotube containing powder into functional macroscale composite materials in the form of fibers 3 and films. [3][4][5] However, these improvements in nanotube based material properties rely on dispersing nanotubes in a polymer based matrix.…”
Section: Introductionmentioning
confidence: 99%